1996
DOI: 10.1042/bj3151027
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of InsP4 and InsP6 binding proteins from human platelets: InsP4 promotes Ca2+ efflux from inside-out plasma membrane vesicles containing 104 kDa GAP1IP4BP protein

Abstract: A low-density membrane fraction from human platelets contained the plasma membrane marker glycoprotein Ib (GpIb) and selective binding sites for InsP4 and InsP6. It was separated from the bulk of InsP3-receptor-containing membranes, but was heterogeneous, probably also containing surface-connected canalicular system and some lighter elements of the internal dense tubule system. After loading with calcium oxalate and re-centrifugation on Percoll gradients, this mixed fraction was subfractionated into light memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 53 publications
4
32
0
Order By: Relevance
“…To date, published data on the role of Ins(1,3,4,5)P 4 in Ca 2ϩ mobilization across plasma membranes remain inconclusive. Although several reports implicated Ins(1,3,4,5)P 4 in mediating Ca 2ϩ entry in certain types of electrically nonexcitable cells such as sea urchin eggs (42), Xenopus oocytes (43), and platelets (44), other studies indicated that Ins(1,3,4,5)P 4 did not have a significant effect, if any, on potentiating Ca 2ϩ influx in other cells like mouse lacrimal acinar cells (45) and Jurkat T cells (33). The data obtained in this study support the latter view that Ins(1,3,4,5)P 4 does not play a role in anti-CD3-or PI(3,4,5)P 3 -elicited Ca 2ϩ influx.…”
Section: Discussionmentioning
confidence: 99%
“…To date, published data on the role of Ins(1,3,4,5)P 4 in Ca 2ϩ mobilization across plasma membranes remain inconclusive. Although several reports implicated Ins(1,3,4,5)P 4 in mediating Ca 2ϩ entry in certain types of electrically nonexcitable cells such as sea urchin eggs (42), Xenopus oocytes (43), and platelets (44), other studies indicated that Ins(1,3,4,5)P 4 did not have a significant effect, if any, on potentiating Ca 2ϩ influx in other cells like mouse lacrimal acinar cells (45) and Jurkat T cells (33). The data obtained in this study support the latter view that Ins(1,3,4,5)P 4 does not play a role in anti-CD3-or PI(3,4,5)P 3 -elicited Ca 2ϩ influx.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that microinjection of Ins(1,3,4,5)P 4 into the whole cells caused [Ca 2ϩ ] i increase through a mechanism dependent on external Ca 2ϩ . In addition, several research groups have isolated an Ins(1,3,4,5)P 4 -binding protein, GAP1 IP4BP , from platelet plasma membranes (47)(48)(49)(50). However, the present study refutes the second messenger role of Ins(1,3,4,5)P 4 in regulating FceRI-mediated Ca 2ϩ inflow in mast cells.…”
Section: Discussionmentioning
confidence: 99%
“…Though roles of GAP1 are not completely clear, its distinct perinuclear localization [18] leads us to expect that GAP1 m might be involved in the transcriptional process. Physiologically, GAP1 has the G protein (Gα12)- [19] and inositol 1,3,4,5-tetrakisphosphate (Ins(1,3,4,5)P 4 )-binding sites [20], and activates inositol tetrakisphosphate (IP 4 )-gated Ca 2+ influx [21]. The same line of evidence is provided by us that bradykinin and Ins(1,3,4,5)P 4 induce continuous Ca 2+ influx in oncogenic ras-transformed NIH/3T3 fibroblast DT cells [22], predicting the up-regulated GAP1 function [23,24].…”
Section: Introductionmentioning
confidence: 99%